Tim X:Y biet
\(\left(x-1\right)^2+\left(y-4\right)^2=0\)
\(\left|x+y+\frac{1}{100}\right|\)\(=-\left|x\right|-\left|y\right|-\left|\frac{1}{10}\right|\)
\(\left|x+1\right|+\left|x+2\right|+\left|x+3\right|+...+\left|x+200\right|=201\)
\(a,-\frac{2}{3}.\left(x-\frac{1}{4}\right)=\frac{1}{3}.\left(2x+1\right)\)
\(b,\frac{1}{5}.2^x+\frac{1}{3}.2^{x+1}=\frac{1}{5}.2^7+\frac{1}{3}:2^8\)
\(c,\left(x-y^2+z\right)^2+\left(y-2\right)^2+\left(z+3\right)^2=0\)
Bài 2 :
a, \(\frac{3}{\left(x+2\right)\left(x+5\right)}+\frac{5}{\left(x+5\right)\left(x+10\right)}+\frac{7}{\left(x+10\right)\left(x+17\right)}=\frac{x}{\left(x+2\right)\left(x+17\right)}\)
b, \(\frac{2}{\left(x-1\right)\left(x-3\right)}+\frac{5}{\left(x-3\right)\left(x-8\right)}+\frac{12}{\left(x-8\right)\left(x-20\right)}-\frac{1}{\left(x-20\right)}=\frac{-3}{4}\)
Bài 1
\(\frac{1}{2}+\frac{1}{2.3}+\frac{1}{3.4}+.......+\frac{1}{x.\left(x+1\right)}=\frac{49}{50}\)
\(\frac{2x+3}{x-1}\)có giá trị là số nguyên \(\left(x\inℤ,x\ne0\right)\)
\(\frac{x-4}{y-3}=\frac{4}{3}\)và \(x-y=5\)\(\left(y\ne3\right)\)
Tìm x,y nguyên dương để: \(\frac{1}{x}+\frac{y}{2}=\frac{5}{8}\)
\(\left(x+3\right)^2+\left(y-1\right)^2< 4\left(x;y\inℤ\right)\)
\(\left(x+3\right)^2.\left(y-3\right)=-4\left(x;y\inℤ\right)\)
1, Tính \(\frac{1}{2}-\left(\frac{1}{3}+\frac{2}{3}\right)+\left(\frac{1}{4}+\frac{2}{4}+\frac{3}{4}\right)-\left(\frac{1}{5}+\frac{2}{5}+\frac{3}{5}+\frac{4}{5}\right)+...+\left(\frac{1}{100}+\frac{2}{100}+\frac{3}{100}+...+\frac{99}{100}\right)\)2,Tính \(\left(1-\frac{1}{2^2}\right)x\left(1-\frac{1}{3^2}\right)x\left(1-\frac{1}{4^2}\right)x...x\left(1-\frac{1}{n^2}\right)\)
\(\frac{1}{\left(x+2\right)\left(x+3\right)}+\frac{1}{\left(x+3\right)\left(x+4\right)}+\frac{1}{\left(x+4\right)\left(x+5\right)}+\frac{1}{\left(x+5\right)\left(x+6\right)}=\frac{1}{8}\)
Tìm x, biết:
\(\frac{3}{\left(x+2\right)\left(x+5\right)}+\frac{5}{\left(x+5\right)\left(x+10\right)}+\frac{7}{\left(x+10\right)\left(x+17\right)}=\frac{x}{\left(x+2\right)\left(x+17\right)}\left(x\notin-2;-5;-10;-17\right)\)
\(\frac{2}{\left(x-1\right)\left(x-3\right)}+\frac{5}{\left(x-3\right)\left(x-8\right)}+\frac{12}{\left(x-8\right)\left(x-20\right)}-\frac{1}{x-20}=-\frac{3}{4}\)
Với \(x\notin1;3;8;20\)
\(\frac{x+1}{10}+\frac{2+1}{11}\frac{x+1}{12}=\frac{x+1}{13}+\frac{x+1}{14}\)
\(\frac{x-10}{30}+\frac{x-14}{43}+\frac{x-5}{95}+\frac{x-148}{8}=0\)
A) \(\frac{3}{\left(X+2\right)\left(X+5\right)}\)+\(\frac{5}{\left(X+5\right)\left(X+7\right)}+\frac{7}{\left(X+10\right)\left(X+17\right)}=\frac{X}{\left(X+2\right)\left(X+17\right)}\)
B) \(\frac{2}{\left(X-1\right)\left(X-3\right)}+\frac{5}{\left(X-3\right)\left(x-8\right)}+\frac{12}{\left(X-8\right)\left(X-20\right)}-\frac{-1}{X-20}=\frac{3}{4}\)